Challenges of accelerated vaccine development - Simon, Jakub (Henry Stewart Talks, 2020)
Vaccine development under normal circumstances, Ebola: virus transmission, disease and outbreaks, Ebola as a case-study for challenges of accelerated vaccine development, Demonstrating safety, efficacy, and manufacturing consistency, Challenges in cutting clinical development from 10+ to 5 years, Vaccine acceleration can be achieved through good partnership